Drug resistance tuberculosis: a global menace - Marahatta, SB (Journal of Manmohan Memorial Institute of Health Sciences, 2014)
DOI: http://dx.doi.org/10.3126/jmmihs.v1i2.9901 Journal of Manmohan Memorial Institute of Health Sciences Vol.1(2) 2013; 1-2